Teaching Religious Moderation through Literature a Teaching-Oriented Reading of Yusuf Azeem is Not a Hero - Dahlan Dahlan (Faculty of Education and Teacher Training of UIN Palopo, 2025)
In the contemporary global context, religious moderation has become an essential educational agenda, particularly in societies marked by religious diversity and historical trauma. Following the September 11, 2001 attacks, Islam and Muslim communities in the United States experienced intensified suspicion, stereotyping, and discrimination, commonly conceptualized as Islamophobia. This condition presents not only a social and political problem but also an educational challenge for universities seeking to promote tolerance, empathy, and peaceful coexistence (Allen, 2010). This teaching-oriented article examines how religious moderation can be taught through literary texts by analyzing Yusuf Azeem Is Not a Hero (2021) by Saadia Faruqi. Employing a qualitative descriptive method and the perspective of genetic structuralism, the study explores the relationship between the author’s social background as a Muslim American, the post-9/11 socio-historical context, and the novel’s narrative strategies in responding to Islamophobia. The analysis reveals that the novel embodies core values of religious moderation, including moral exemplarity, courage in articulating religious identity, tolerance and interfaith interaction, and literature as a medium of peacebuilding. By reconstructing the analysis into a pedagogical framework, this article demonstrates that literature can function as an effective learning resource for teaching religious moderation in higher education. The findings contribute to literary studies, religious education, and curriculum development by positioning fiction as a transformative tool for countering religious prejudice and fostering inclusive citizenship.